Lower anti-Müllerian hormone levels are associated with HIV in reproductive age women and shorter leukocyte telomere length among late reproductive age women. (1st April 2023) - Van Ommen, Clara E.; Hsieh, Anthony Y.Y.; Albert, Arianne Y.; Kimmel, Elana R.; Cote, Helene C.F.; Maan, Evelyn J.; Prior, Jerilynn C.; Pick, Neora; Murray, Melanie C.M.
Abstract : Objectives: We sought to better understand factors associated with ovarian aging in women with HIV (WWH). Design: HIV has been associated with diminished fertility, younger age at menopause, and shorter leukocyte telomere length (LTL), a marker of cellular aging. We herein examine cross-sectional and longitudinal associations between LTL, anti-Müllerian hormone (AMH), and HIV. Methods: We included WWH and HIV-negative women 12–50 years of age in the CARMA cohort with one or more study visit(s). LTL and AMH were measured by qPCR and ELISA, respectively. Women were analyzed in peak reproductive (<35 years) vs. late reproductive (≥35 years) life phases. Using multivariable mixed-effect linear or logistic regressions, we assessed factors associated with AMH and ΔAMH/year while adjusting for relevant confounders. Results: WWH had shorter LTL and lower AMH levels compared to HIV-negative controls despite being of similar age. After adjusting for relevant factors, HIV was associated with 20% lower AMH levels in women under 35 years of age and shorter LTL was associated with AMH levels below 2 ng/ml among women aged 35 years or older. Longitudinally, ΔAMH/year was largely related to initial AMH level among older women, and to age in younger women. Conclusions: Factors associated with AMH change across women's reproductive lifespan. Lower AMH among peak reproductive aged WWH suggests that HIV may have an initial detrimental effect on ovarian reserve, an observation that may warrant counseling around pregnancy planning. In women aged 35 years or older, the association between shorter LTL and lower AMH suggests that the immune and reproductive aging connections are more important in this age group.